Monitoring of Bainite Transformation Using in Situ Neutron Scattering - Hikari Nishijima; Yo Tomota; Yuhua Su; Wu Gong; Jun-ichi Suzuki (Metals, 2016)
Bainite transformation behavior was monitored using simultaneous measurements of dilatometry and small angle neutron scattering (SANS). The volume fraction of bainitic ferrite was estimated from the SANS intensity, showing good agreement with the results of the dilatometry measurements. We propose a more advanced monitoring technique combining dilatometry, SANS and neutron diffraction.